2013
DOI: 10.1016/j.enggeo.2013.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the compression behaviour of reconstituted clays

Abstract: The void index is a relative quantity measuring the position of the current void ratio of a clay against the void ratios of the clay at two specific vertical effective stresses (i.e., σ v ′ = 100 kPa and σ v ′ =1000 kPa). Based on this concept, a simple systematic tool is proposed for estimating the compression behaviour of reconstituted clays over a wide range of stresses and water contents. Following the practice of geotechnical engineering computation, the compression behaviour of clays is idealised as line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 55 publications
(12 citation statements)
references
References 50 publications
2
10
0
Order By: Relevance
“…Figure 3 indicates that there were three segments of slope from the e versus log σ' curves for the three respective drainage conditions. These findings are in agreement with recent observations by Liu, Zhuang, and Horpibulsuk (2013). The first segment was found at an effective stress of less than 12 kPa.…”
Section: Settlement and Pore Pressuresupporting
confidence: 94%
See 2 more Smart Citations
“…Figure 3 indicates that there were three segments of slope from the e versus log σ' curves for the three respective drainage conditions. These findings are in agreement with recent observations by Liu, Zhuang, and Horpibulsuk (2013). The first segment was found at an effective stress of less than 12 kPa.…”
Section: Settlement and Pore Pressuresupporting
confidence: 94%
“…As such, the compression of ultra-soft soils at very low effective stresses is dependent upon initial level of water content. Liu, Zhuang, and Horpibulsuk (2013) analyzed compression curves of various reconstituted clays with high water contents. The authors found that beyond a specific stress level, designated herein as transition pressure, the compression curves are unique and can be approximated using the intrinsic compression line (ICL) proposed by Burland (1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is apparent that the ICL defined for the Singapore marine clay is similar to that proposed by Burland (1990). The deviation at low stresses of less than 100 kPa could be due to the difference between the initial moisture content of the various tested samples with slightly different liquid limit varying between 77 and 84% as observed by Hong, Yin, and Cui (2010), Liu and Carter (2010), Liu, Zhuang, and Horpibulsuk (2013) and Horpibulsuk et al (2016). The intrinsic compression index obtained from the ICL is in the range of 0.58 to 0.67.…”
Section: Intrinsic Behaviorsupporting
confidence: 68%
“…There has been a large amount of theoretically modelling and prediction of the compression behaviour of soils including the influence of soil structures [4,[25][26][27]39]. However, theoretical models capturing the compression behaviour of metal-rich clays are very limited [12].…”
Section: Introductionmentioning
confidence: 99%